Molecular Changes in Aqueous Humor Associated with Inflammation Following Cataract Surgery in Patients with Fuchs’ Endothelial Corneal Dystrophy - Lizaveta Chychko; Hyeck-Soo Son; Maximilian Friedrich; Ramin Khoramnia; Gerd U. Auffarth; Victor A. Augustin (Ophthalmology and Therapy)
Abstract Introduction To evaluate the anterior chamber (AC) inflammation in the early postoperative period after cataract surgery and before Descemet membrane endothelial keratoplasty (DMEK) by quantifying oxidative stress and inflammatory mediators in aqueous humor of patients with Fuchs’ endothelial corneal dystrophy (FECD). Methods In this prospective single-center study, 15 patients with FECD underwent cataract surgery and DMEK in a two-stage procedure. Aqueous humor was collected from the AC at the beginning of cataract surgery and 3 months later at the beginning of DMEK. In the control group, which consisted of 15 age-matched phakic patients without FECD, aqueous humor was only collected at the beginning of cataract surgery. Mediators of postoperative inflammation including TNF-α, VEGF, IL-2, IL-1 β, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, GM-CSF, IFN-γ, CXCL5/ENA-78, FGF-basic, G-CSF, IL-1-α, IL-1-ra, IL-17, CCL2/MCP-1, CCL3/MIP-1a, CCL4/MIP-1b, TPO, TGF-β-1, TGF-β-2, and TGF-β-3 concentrations were measured using a Multiplex-Array-System. Results The concentration of TNF-α (p = 0.021), IL-6 (p = 0.005), IL-8 (p = 0.001), CXCL5/ENA78 (p = 0.002), CCL2/MCP-1 (p = 0.001) and CCL4/MIP-1b (p = 0.037) were significantly higher 3 months after cataract surgery at the beginning of DMEK compared to control group at beginning of cataract surgery. The levels of IL-2, IL-5, IL-8, IL-10, and IL-1-α were significantly higher in phakic eyes in the control group (p < 0.05) before cataract surgery. Conclusions The present study indicates significantly increased proinflammatory cytokines 3 months after cataract surgery in eyes with FECD. Our findings suggest postoperative inflammation in the AC up to 3 months after cataract surgery. Therefore, it may be reasonable to combine cataract surgery with DMEK in cataract patients with FECD.